Electric Filed Intensity of the Lightning Strikes on Lightning Air Terminals Installed on Building Structures - Irshad Ullah; MNR Baharom; H.M. Luqman; H. Ahmad; Zainab Zainal (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Lightning activities are growing up rapidly with global warming. It can affect anything on the earth. All the constructed buildings need proper protection from the harmful effect of lightning. Lightning strike points on different geometrical shapes have been investigated. Lightning strike distribution of different building structure is very important to be studied. In order to analyse the maximum effect of lightning strike pattern is obtained of different air terminals installed on scaled building structures. High voltage impulse generator is used in order to get the impulse voltage. Different numbers of air terminals have been applied to all the shapes in order to see the lightning strike points. Electric field is obtained in order to see its minimum and maximum effect on the entire building structure. Interestingly the phenomenon of lightning air terminal bypasses has been proved in this paper.